Lexicographic multi-objective MPC for constrained nonlinear systems with changing objective prioritization. (March 2021) - He, Defeng; Li, Haiping; Du, Haiping
Abstract: This paper proposes a new lexicographic multi-objective model predictive control (MoMPC) scheme for constrained nonlinear systems with changing objective prioritization. The lexicographic optimization-based receding horizon optimal control problem is firstly formulated to accommodate the concern on prioritized control of multiple (economic) objectives. Then an elaborate generic function and the notion of general terminal constraints are introduced to regain feasibility of lexicographic MoMPC in the presence of constraints and changing objective prioritization. Moreover, the LaSalle invariance set theorem is used to establish stability of the closed-loop system with the lexicographic MoMPC. An example of a coupled-tank level control problem with three conflicting objectives is adopted to demonstrate the effectiveness of the proposed scheme.